Penn State Worry Questionnaire (PSWQ 11): Psychometric Evidence in a Sample of Adults in Metropolitan Lima. - Carbonell-Bártoli , Enzo Lucciano (2022)
The Penn State Worry Questionnaire (PSWQ 11) is a measure that assesses the tendency to experience worry. The present study aimed to analyze the psychometric properties of the PSWQ 11 in the adult population of Lima, Peru. The sample consisted of 535 adults aged 18 to 55 years (M= 25.13, SD= 7.03). Descriptive statistics were analyzed, finding normal distributions in all items, as well as adequate corrected item-test correlations. The internal structure analysis showed adequate fit indices for a model with item covariance (χ²/gl= 4.32; CFI= .99; TLI= .99; RMSEA= .08; SRMR= .03; WRMR= .95). Likewise, the analysis of the relationships with other variables demonstrated the convergent and discriminant validity of the PSWQ 11 in relation to the PANAS. Also, an alpha coefficient of .94 was obtained, demonstrating that the measure is reliable. Finally, the factorial invariance of the instrument by sex and age was demonstrated, showing no differences in the evaluation of worry in these groups.